2022
DOI: 10.3390/microorganisms11010070
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pneumococcal Serotypes in Community-Acquired Pneumonia among Older Adults in Italy: A Multicenter Cohort Study

Abstract: Pneumococcal community-acquired pneumonia (CAP) is a leading cause of mortality. Following the introduction of pneumococcal conjugate vaccines (PCVs) in children, a decrease in the burden of the disease was reported. In parallel, an increase in non-vaccine serotypes was also noted. The objective of this study was to assess the current serotype-specific epidemiology of pneumococci among Italian older adults hospitalized for CAP. A prospective study was conducted between 2017 and 2020 in four Italian regions. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…However, the JCVI “recently agreed that either PCV20 or PPV23 could be used for the adult pneumococcal programme.” “The Committee also indicated that PCV20 was likely to prevent more disease than PPV23 and waning of immunity may occur at a slower rate.” 27 In our study a further 5% of pneumococcal CAP was attributed to the additional PCV15 serotypes and almost a quarter due to a unique PCV20 (non-PCV13) serotype. This is in accordance with the findings of other recent European studies, 28 , 29 , 30 and suggests that potentially considerable numbers of pneumococcal CAP could be averted with the higher-valency vaccines.…”
Section: Discussionsupporting
confidence: 93%
“…However, the JCVI “recently agreed that either PCV20 or PPV23 could be used for the adult pneumococcal programme.” “The Committee also indicated that PCV20 was likely to prevent more disease than PPV23 and waning of immunity may occur at a slower rate.” 27 In our study a further 5% of pneumococcal CAP was attributed to the additional PCV15 serotypes and almost a quarter due to a unique PCV20 (non-PCV13) serotype. This is in accordance with the findings of other recent European studies, 28 , 29 , 30 and suggests that potentially considerable numbers of pneumococcal CAP could be averted with the higher-valency vaccines.…”
Section: Discussionsupporting
confidence: 93%
“…The findings from the urine antigen method in our study are similar to a previous study done in the same setting between 2005 and 2007, that reported pneumococcus in 23% of the adults hospitalized with pneumonia 17 , albeit higher compared with studies from Italy 18 and Thailand 19 , that reported S. pneumoniae in 13% and 8–11% of hospitalized adults with CAP, respectively. Furthermore, while the urine antigen test in our study was found to be more sensitive at detecting S. pneumoniae compared with the other methods, these results should be interpreted with caution as other studies have found that a proportion of patients with positive blood or sputum cultures have negative antigen tests 20 , antigens may cross-react with closely related streptococci species, and urine antigens can be positive for weeks after the onset of disease 10 , 21 .…”
Section: Discussionsupporting
confidence: 90%
“…With regard to the attribution of disease cases to the different serotypes, for invasive pneumococcal diseases (IPDs) reference was made to the data collected (year 2019, 2020) by the ISS [3]; for pneumococcal CAP (P-NBP) evidence from the PUMA study [21] was used, considering a proportion of P-NBP of 15.1% for the population aged 65-74 years (Table 2).…”
Section: Composition Of Disease Cases By Serotypementioning
confidence: 99%